Hygienic-Sanitary and Good Manufacturing Evaluation of Chicken Cuts Marketed In Chókwè City - Massingue Junior, Abel; Sigauque, Francisco José Luís; Machalela, Angélica Agostinho; José, António Elísio; Nanelo, Rafael Francisco (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
This study assessed the hygiene and health conditions of chicken cuts sold in Chókwè city. The checklist method was applied following Resolution RDC No. 216/04 to assess the hygiene and health conditions, verifying the adequacy or otherwise of the items evaluated. When the checklist was completed, the following was considered: (C)